A genomic can of worms for schistosome host-specificity. Issue 7 (July 2022) - Nikolakis, Zachary L.; Carlton, Elizabeth J.; Pollock, David D.; Castoe, Todd A.
Abstract : Understanding the genetic underpinnings of schistosome host preferences is critical. Luo et al . recently identified genes associated with intermediate and definitive host-switching based on a new chromosome-level genome for Schistosoma japonicum, population genetic comparisons, and follow-up experiments. This represents a guide to fully map-selected schistosome genes using population genetics.